2018
DOI: 10.1016/j.foodpol.2017.11.007
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cash transfers and household vulnerability on food security in Zimbabwe

Abstract: We study the impact of the Zimbabwe Harmonized Social Cash Transfer (HSCT) on household food security after 12 months of implementation. We investigate determinants of food security as measured by a well-known food security scale – the Household Food Insecurity Access Scale (HFIAS) – and as measured by value of household food consumption composed of own-production, market purchases and gifts received. We find that several dimensions of household vulnerability correlate more strongly with the food security meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 18 publications
0
46
0
2
Order By: Relevance
“…The scale of a farm business encourages farm and production diversity [77]. It is also an important source of improved cash income, wealth, and earnings, which increases economic access to diverse foods and consumption of quality and diversified diets [44,82,[88][89][90][91].…”
Section: Discussionmentioning
confidence: 99%
“…The scale of a farm business encourages farm and production diversity [77]. It is also an important source of improved cash income, wealth, and earnings, which increases economic access to diverse foods and consumption of quality and diversified diets [44,82,[88][89][90][91].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings also suggested a significant relationship between food insecurity and formal education of household head. These results imply that education is important for improving the food security status of farmers as the educated farmers were less likely to be food insecure (Li and Yu, 2010;Bhalla et al, 2018). Previous studies showed that formally educated respondents had a better food security score than those without formal education (Li and Yu, 2010;Bhalla et al, 2018).…”
Section: Determinants Of Respondent's Food Insecuritymentioning
confidence: 72%
“…These results imply that education is important for improving the food security status of farmers as the educated farmers were less likely to be food insecure (Li and Yu, 2010;Bhalla et al, 2018). Previous studies showed that formally educated respondents had a better food security score than those without formal education (Li and Yu, 2010;Bhalla et al, 2018). In fact, the low level of formal education is strongly associated with the probability of experiencing food insecurity (Maxwell et al, 2014).…”
Section: Determinants Of Respondent's Food Insecuritymentioning
confidence: 83%
See 1 more Smart Citation
“…In ten countries in SSA (Ethiopia, Kenya, Lesotho, Malawi, Mozambique, Nigeria, South Africa, Uganda, Zambia and Zimbabwe), food security improved because of receiving CTs as most of the transfer income was spent on food. Most beneficiary households also improved their diet diversity (Berhane et al, 2015, Bhalla et al, 2018, Brugh et al, 2018, Carneiro et al, 2017, Case, 2004, d'Agostino et al, 2017, Handa et al, 2013b, Haushofer and Shapiro, 2016, Miller and Tsoka, 2008, OPM, 2013, 2015, Soares and Teixeira, 2010. Evidence from LA also shows that CTs increased household consumption, in particular food consumption, and households improved their diet diversity.…”
Section: Cash Transfers and Underlying Determinants Of Child Nutritionmentioning
confidence: 99%